AB1058 CO-DESIGNING A COMPARATIVE RANDOMISED CONTROLLED CLINICAL TRIAL OF CORTICOSTEROID REGIMENS WITH CHILDREN, YOUNG PEOPLE AND PARENTS LIVING WITH JUVENILE IDIOPATHIC ARTHRITIS. (June 2019) - Stones, Simon; Bagley, Heather; Sherratt, Frances; Roper, Louise; Baildam, Eileen; ,
Abstract : Background: Previous research has identified the need for a randomised controlled trial (RCT) evaluating the most appropriate corticosteroid induction regimen to be used for children and young people (CYP) with juvenile idiopathic arthritis (JIA) (1). A recent qualitative study found that parents and CYP understood trial concepts and were able to identify potential flaws in a proposed RCT. This confirms the need to involve parents and CYP in co-designing RCTs to best meet the needs of future trial participants (2). Objectives: To co-design components of an RCT of corticosteroid regimens with CYP and parents living with JIA. Methods: A focus group was conducted with CYP with JIA and parents as part of a wider consensus and discussion group meeting within the Steroid Induction Regimen for Juvenile Idiopathic Arthritis (SIRJIA) study in December 2018. The discussion focused on two components of the RCT design: i) Discussing the most appropriate treatment protocols; and ii) Addressing practicalities associated with an RCT. Results: Two RCT protocol options, chosen through an online survey by a clear majority out of a possible eight protocols, were discussed and critiqued: i) Protocol A (intravenous vs intraarticular corticosteroid delivery); and ii) Protocol B (intravenous vs intraarticular vs intramuscular vs oral corticosteroid delivery). Several issues pertaining to both protocols were raised, related to the influence of age and past experience, routes of administration and concerns over randomisation. Participants emphasised the importance of clinicians/researchers discussing all of the potential risks with them. Participants also wanted enough information to make an informed choice. Participants emphasised the usefulness of combining trial visits with regular follow-up appointments to minimise the burden of taking part in an RCT and had a preference for their usual hospital being the site they visited. Some participants remarked that videos could be a useful way of conveying information beyond traditional participant information sheets. Some also felt that awareness of research opportunities is not equally accessible to them either, depending on where they lived in the country. Participants would want to be kept regularly updated about the progress of the RCT and felt that incentives were a good way of keeping people engaged, although some were trepidatious to hear negative treatment results. With regards to dissemination, participants felt that study results should be readily available to them in an accessible format, should they wish to view them. Conclusion: CYP and parents have a considerable amount of knowledge and experience which can shape the design of RCTs. With adequate support, complex concepts such as treatment protocols can be discussed and critiqued. Involving CYP and parents at the design stage of an RCT has been shown to eliminate some potential challenges in the future. References: [1] Deepak, et al. (2017). Literature review on the use of corticosteroids in juvenile idiopathic arthritis (JIA). Rheumatology 56(Suppl7). [2] Sherratt FC, et al. (2018). Protective parents and permissive children: what qualitative interviews with parents and children can tell us about the feasibility of juvenile idiopathic arthritis trials. Pediatric Rheumatology 16:76. Acknowledgement: This activity was funded as part of the SIRJIA study, funded by the NIHR Health Technology Assessment Programme (14/167/01). The funders did not have a role in the design, collection, analysis, or interpretation of the data. Disclosure of Interests: Simon Stones Consultant for: SS has provided consultancy services to Envision Pharma Group, though this is not related to the contents of this abstract., Speakers bureau: SS has undertaken speaking engagements for Actelion, eyeforpharma, Four Health, Janssen and Roche, though these are not related to the contents of this abstract., Heather Bagley: None declared, Frances Sherratt: None declared, Louise Roper: None declared, Eileen Baildam Consultant for: EB has received one paid consultancy for Pfizer in the last 12 months, but this was not related to this study.